Work-Related Musculoskeletal Disorders and Associated Factors Among Bankers in Ethiopia, 2018 - Alemu Kasaw Kibret; Berihu Fisseha Gebremeskel; Kebede Embaye Gezae; Gebrerufael Solomon Tsegay (Pain Research and Management)
Background. Work-related musculoskeletal disorders (WMSDs) are an important public health problem in working environments. WMSDs are the major causes of disability and cause individual suffering and financial burdens to the individual, families, industry or employer, healthcare system, and society at large. This study aims to assess the prevalence and associated factors of work-related musculoskeletal disorders among bankers working in Mekelle city, Tigray, Ethiopia, 2018. This study is based on an institutional-based cross-sectional study design, where 328 bankers are selected randomly from bankers working in Mekelle city from February to June 2018. Data were entered, organized, and analyzed by SPSS version 23. A final logistic model was run to identify factors associated with WMSDs, and the magnitude and direction of association were decided based on the adjusted odds ratio (AOR) and its corresponding 95% confidence interval (95% CI). Result. Out of 307 bankers, the annual prevalence rate of WMSDs was 65.5% (201). Significant predictors were being 30–39 years old [AOR = 5.552; 95% CI = 1.465–21.039] and above 40 years old [AOR = 5.719; 95% CI = 1.422–22.994], low educational level [AOR = 4.256; 95% CI = 1.139–15.895], working > 5 years [AOR = 3.892; 95% CI = 1.841–8.231], not doing physical exercises [AOR = 2.866; 95% CI = 1.303–6.304], stress [AOR = 4.723; 95% CI = 2.421–9.213], poor posture [AOR = 2.692; 95% CI = 1.339–5.411], breaks [AOR = 5.170; 95% CI = 2.070–12.912], and ergonomics [AOR = 3.801; 95% CI = 1.260–11.472]. Conclusion. The prevalence of WMSDs among bankers was high. The significant associated factors responsible for the occurrence of work-related musculoskeletal disorders include longer working experience, being above 30 years old, low educational status, physical exercise, job stress, poor posture, absence of breaks during working hours, and absence of ergonomic training.